Phthalate metabolism in Pseudomonas testosteroni: accumulation of 4,5-dihydroxyphthalate by a mutant strain. - Nakazawa, T (1977)
A mutant strain of Pseudomonas testosteroni blocked in phthalate catabolism converted phthalate into 4,5-dihydroxyphthalate. The latter compound was isolated, and its physical properties were determined. A stoichiometric conversion of the compound to protocatechuate was demonstrated spectrophotometrically with crude extracts of a protocatechuate 4,5-dioxygenase-deficient mutant. Therefore, phthalate is metabolized through 4,5-dihydroxyphthalate and protocatechuate, which is further degraded by protocatechuate 4,5-dioxygenase in P. testosteroni. By using several mutants blocked in phthalate catabolism, 4,5-dihydroxyphthalate decarboxylase was shown to be induced by phthalate. A simple spectrophotometric assay for the enzyme is also reported.